Elimination of large tumors in mice by mRNA-encoded bispecific antibodies - Stadler, Christiane R; Bähr-Mahmud, Hayat; Celik, Leyla; Hebich, Bernhard; Roth, Alexandra S; Roth, René P; Karikó, Katalin; Türeci, Özlem; Sahin, Ugur (Nature medicine, 2017)
Bispecific antibodies that connect T cells with tumor cells can be delivered in the form of in vitro –transcribed pharmacologically optimized mRNA; when injected into mice, these mRNA-encoded antibodies reject large established tumors as efficiently as the corresponding recombinant antibody protein. The potential of bispecific T cell–engaging antibodies is hindered by manufacturing challenges and short serum half-life. We circumvented these limitations by treating mice with in vitro –transcribed pharmacologically optimized, nucleoside-modified mRNA encoding the antibody. We achieved sustained endogenous synthesis of the antibody, which eliminated advanced tumors as effectively as the corresponding purified bispecific antibody. Because manufacturing of pharmaceutical mRNA is fast, this approach could accelerate the clinical development of novel bispecific antibodies.